Redetermination of orotic acid monohydrate - Portalone, Gustavo (International Union of Crystallography, 2008)
The crystal structure of the title compound, which is also known as vitamin B(13) (systematic name: 2,6-dioxo-1,2,3,6-tetrahydropyrimidine-4-carboxylic acid monohydrate), C(5)H(4)N(2)O(4)·H(2)O, was reported for the first time by Takusagawa & Shimada [Bull. Chem. Soc. Jpn (1973 ▶), 46, 2011–2019]. The present redetermination provides more precise values of the molecular geometry. The asymmetric unit comprises a planar diketo tautomer and a solvent water molecule. In the crystal structure, molecules are connected by O—H⋯O, N—H⋯O and C—H⋯O hydrogen bonds involving NH groups, two carbonyl O atoms and the solvent water molecule.